2022
DOI: 10.1055/a-1873-2150
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Gland Function and Dysfunction During COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) pandemic is currently one of the major health concerns worldwide accounting for many deaths and posing a great social and economic burden. Early activation of adrenal hormone secretion is pivotal to surviving systemic microbial infections. In addition, clinical studies demonstrated that glucocorticoids might also be beneficial in reducing disease progression and life deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 87 publications
1
12
0
3
Order By: Relevance
“…An adequate and balanced response to stress is detrimental to human health as excessive or chronic activation of the hypothalamus-pituitary-adrenal axis and the sympathoadrenal system, also known as the endocrine stress system, is associated with the pathogenesis of various human diseases and psychological disorders, including metabolic syndrome, anxiety, or post-traumatic stress disorder (PTSD) 2 3 4 5 . Recent studies have demonstrated that patients with severe COVID-19 have a pronounced elevation in the plasma stress hormones 6 . Interestingly, an elevation of adrenal glucocorticoids in the plasma might persist long after the initial infection with coronavirus, as shown in the case of survivors of the SARS-CoV-1 pandemic 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An adequate and balanced response to stress is detrimental to human health as excessive or chronic activation of the hypothalamus-pituitary-adrenal axis and the sympathoadrenal system, also known as the endocrine stress system, is associated with the pathogenesis of various human diseases and psychological disorders, including metabolic syndrome, anxiety, or post-traumatic stress disorder (PTSD) 2 3 4 5 . Recent studies have demonstrated that patients with severe COVID-19 have a pronounced elevation in the plasma stress hormones 6 . Interestingly, an elevation of adrenal glucocorticoids in the plasma might persist long after the initial infection with coronavirus, as shown in the case of survivors of the SARS-CoV-1 pandemic 7 .…”
Section: Introductionmentioning
confidence: 99%
“…
Recent studies have demonstrated that patients with severe COVID-19 have a pronounced elevation in the plasma stress hormones [6]. Interestingly, an elevation of adrenal glucocorticoids in the plasma might persist long after the initial infection with coro-Review
…”
mentioning
confidence: 99%
“…Some authors 25 have suggested that primary adrenal gland insufficiency specifically may be underdiagnosed among PASC. COVID-19 infection may impact the adrenal glands by both direct and indirect mechanisms.…”
Section: Introduction/history/definitions/backgroundmentioning
confidence: 99%
“…From a cellular level, SARS-CoV-2 binds preferentially to angiotensin converting enzyme 2 (ACE 2). Various studies have suggested that ACE 2 is expressed on adrenal glands and that SARS-CoV-2 may have a propensity to replicate within these cells 25 . However, there has been no direct evidence of cellular damage in these tissues.…”
Section: Introduction/history/definitions/backgroundmentioning
confidence: 99%
“…In the second part of this issue, aspects linking endocrine diseases with COVID-19 are presented. Specifically, Kanczkowski et al [6] describe how COVID-19 infection may cause adrenal gland damage both directly and indirectly and how it may impair adrenal gland function both in the short-as well as in the long-term. Tsourdi et al [7] summarize the evidence from preclinical models and clinical studies about the effects of COVID-19 and its treatments on bone metabolism and they discuss how osteoporosis medications may have beneficial effects on the clinical course of COVID-19.…”
mentioning
confidence: 99%